Rural Development in India: Through Employment Programmes - Giri, Ashok Kumar (International Journal of Scientific Research and Management (IJSRM), 2017)
Poverty alleviation has been one of the objective of the employment generation programmes in India since independence. The five year plans immediately after independence tried to focus on poverty alleviation through sectoral programmes . The second and third five year plans focused on massive state led investments for employment generation in public sector. Government of India has been running many poverty alleviation programmes and some success also achieved in this endeavour over the years. However, even today Government struggle with mass level of poverty and related problems. In this context , the Indian Govt. has implemented MGNREGA. Its introduction was a paradigm shift in India’s history of wage employment generation. It is the country’s largest wage- employment programme